From Carlo to Baldassarre Fontana: that is, the evolution of the stucco Baroque language between the Church State and central-northern Europe. Dialogues between architecture and plastic decoration - Federico Bulfone Gransinigh (In Gremium. Studies in History, Culture and Politics, 2021)
The Fontana family, which has always been known as an exponent of architecture and stucco decoration between the 17th and 18th centuries, has in Carlo Fontana the greatest representative in the field of architecture. Carlo collaborated in many projects with the sculptor, plasterer and decorator Antonio Raggi, who was also the master of Carlo’s cousin, Baldassarre Fontana. With this article we would like to outline the relationship between the decorations and the architectures of Carlo Fontana and the continuity and discontinuity of this relationship also implemented by his cousin Baldassarre. The contacts with many plasterers, coming from the territories of northern Italy and Switzerland, also requested by Carlo, allowed both the use of “known” labour within the construction sites followed by Fontana and a dissemination of knowledge of stucco’s art in central Italy. This task was also carried out by the sculptor and plasterer Raggi, who worked with the architect from Rancate and played an important role in Baldassarre Fontana’s stylistic training. Baldassarre also experimented with late Baroque languages in the Moravian and Polish construction sites. The plastic arts are a common thread that accompanies both the “genealogy” of the Fontana family and the architectures that were designed and decorated by it.